NAMPT regulates mitochondria biogenesis via NAD metabolism and calcium binding proteins during skeletal muscle contraction - Kim, Jeong Seok (J Exerc Nutrition Biochem, 2014)
[PURPOSE]: The purpose of this study was to investigate the effect that muscle contraction induced NAD metabolism via NAMPT has on mitochondrial biogenesis. [METHODS]: Primary skeletal muscle cells were isolated from the gastrocnemius in C57BL/6 mice. The muscle cells were stimulated by electrical current at 1Hz for 3 minutes in conditions of normal or NAD metabolism related inhibitor treatment. NAD/NADH level, Sirt1 and mitochondria biogenesis related signal factor’s changes were examined in normal or NAD metabolism related inhibitor treated cells. [RESULTS]: Electrical stimulation (ES) induced muscle contractions significantly increased NAD/NADH levels, NAMPT inhibitor FK-866 inhibited ES-induced NAD formation, which caused SIRT1 expression and PGC-1α deacetylation to decrease. Moreover, NAMPT inhibition decreased mitochondrial biogenesis related mRNA, COX-1 and Tfam levels. Along with AMPK inhibitor, compound C decreases SIRT1 expression, PGC-1α deacetylation and muscle contraction induced mitochondrial biogenesis related mRNA increment. These results indicated that the AMPK-NAMPT signal is a key player for muscle contraction induced SIRT1 expression and PGC-1α deacetylation, which influences mitochondrial biogenesis. Inhibition of the AMPK upregulator, Camkkβ, STO-609 decreased AMPK phosphorylation and SIRT1 expression but did not decrease PGC-1α deacetylation. However, CAMKII inhibition via AIP decreased PGC-1α deacetylation. [CONCLUSION]: In conclusion, the results indicate that NAMPT plays an important role in NAD metabolism and mitochondrial biogenesis. However, mitochondrial biogenesis is also controlled by different calcium binding protein signals including Camkkβ and CAMKII. [Keyword] Muscle contraction, NAD metabolism, SIRT1, PGC-1 α, mitochondria biogenesis.